ICT Integration in Low-resourced English Classrooms in Nepal (Tribhuvan Journal, 2025)
Integrating Information and Communication Technology (ICT) in English Language Teaching (ELT) at the secondary level in Nepal presents a unique set of challenges and opportunities. While infrastructure limitations are significant, a strategic approach focused on mobile technology, offline resources, and pedagogical shifts can significantly enhance student engagement and the development of communicative competence. This paper explores the current situation, key challenges, and practical, low-cost possibilities of ICT integration in Nepalese secondary ELT classrooms. The researcher used a questionnaire and received data from different teachers across the country, and drew findings after analyzing them. The study identified various classroom practices using easily available ICT tools and offers ways of mitigating the solutions of digital divide, which are transferable to low-resource classroom contexts. The study reveals a picture of pragmaticoptimism as Nepali English teachers overwhelmingly perceive ICT as valuable for making ELT more engaging and relevant, and enable a basic level of integration where smartphones, a few laptops and multi-media projectors are available.